The DESCRIPTION OF INTRADIALYSIS COMPLICATIONS IN HEMODIALYSIS PATIENTS BASED ON THE LEVEL OF INTERDIALYTIC WEIGHT GAIN (IDWG) - Muhammad Putra Ramadhan; Krisna Yetti; Tuti Herawati; Muhamad Adam; Achmad Masfi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hemodialysis is the most preferred renal replacement therapy. Besides having a therapeutic effect, hemodialysis also has side effects, namely intradialysis complications. The intradialysis complications are related to Interdialytic Weight Gains (IDWG) because if patient have higher IDWG level, make more fluid will be excreted during hemodialysis. The purpose of this study was to determine the description of intradialysis complications based on the IDWG level. This research used a descriptive design involving 90 hemodialysis patients in one of hospitals in Malang. The data collection technique was carried out by observing the patient every hour during hemodialysis. The results of this study indicate that the higher the IDWG level, the higher the number and frequency of intradialysis complications. Nurses need to optimize their role in assessing, monitoring, planning and documenting patients undergoing hemodialysis so that they can reduce and prevent problems that may be experienced by patients during hemodialysis.